COOKING CHARACTERISTICS AND SENSORY QUALITIES OF COOKED RICE (ORYZA SATIVA L. VAR NSIC RC218) AS INFLUENCED BY WATER AND FERTILIZER APPLICATIONS - Cagasan, Ulysses A; Daclag, Jocelyn G (Journal of Agriculture and Technology Management, 2020)
Cultural practices such as fertilizer and water applications affect the amylose and protein contents of grains in rice which in turn influence the aroma and flavor of the cooked rice.  This study aimed to (1) assess the cooking characteristics of lowland rice NSIC Rc218 as influenced by water and fertilizer applications; (2) assess the sensory qualities of lowland rice NSIC Rc218 as influenced by water and fertilizer applications and (3) determine the interaction effects of water and fertilizer applications in all growth parameters studied. Results of the study found that volume expansion ratio (VER) and water uptake (WU) of NSIC Rc218 cooked rice had significantly ( p <0.05) higher when rice plants were planted in flooded conditions and applied with vermicast at 10 t ha -1 . Elongation ratio (ER) was significantly ( p <0.05) higher (3.26) under flooded condition regardless of fertilizer applied.  Sensory ratings for color, aroma, tenderness, and general acceptability of cooked NSIC Rc218 rice were significantly ( p <0.05) enhanced when rice plants were subjected to AWD conditions and applied with vermicast alone at 10 t ha -1 or without fertilizer application.  Moreover, only volume expansion ratio (VER) and water uptake (WU) of NSIC Rc218 cooked rice had a significant ( p <0.05) interaction effects on water and fertilizer applications.